Long-Gap Esophageal Atresia Gross Type C and D: A Retrospective Study of Surgical Management and Postoperative Complications Within the First Year of Life in the Nordic Countries - Ann Christine Waarkjær Olsen; Antti Koivusalo; Ragnhild Emblem; Audun Mikkelsen; Jan F. Svensson; Anna Maria Tollne; Markus Almström; Linus Jönsson; Helene Lilja; Felipe Donoso; Thorstein Sæter; Jørgen Mogens Thorup; et al. (Children)
Objective: Several surgical approaches are being used in the reconstruction of long-gap esophageal atresia. We investigated which methods are being used in the Nordic countries and the postoperative complications that occurred in the first year of life. Methods: This study is a retrospective multicenter study, where medical records on children with esophageal atresia Gross type C or D born in the period from 1 January 2000 to 1 May 2017 were reviewed. Results: Forty-four patients were included in this study, forty-three with Gross type C and one with Gross type D. Thirty-six patients were included in the statistical analysis. Delayed esophageal anastomosis was performed in half of the patients and an esophageal replacement procedure in the other half. Postoperative complications were common, but there was no difference in postoperative complications or weight-gain within the first year of life. There were no differences in hospital stay or duration of parenteral nutrition. Attempted primary esophageal anastomosis was significantly more common in patients that underwent an esophageal replacement procedure compared to those who underwent a delayed esophageal anastomosis. Conclusions: No significant relationship between surgical approach and postoperative complications within the first year of life could be demonstrated. Long-term functional studies are warranted.